Etika dan Metode Menuntut Ilmu Perspektif Hadits Nabi Muhammad: Ethics and Methods of Demanding Knowledge from the Perspective of the Hadith of Prophet Muhammad - Choirun Nisa, Shifa; Novita Pamujianti, Ayu; Agung Purnomo, Ari; Abbas , Ngatmin (CV. Kalimasada Group, 2024)
This study aims to explore how the principles of ethics and methods of seeking knowledge in hadith can be integrated into the Islamic education curriculum to achieve holistic development encompassing moral, intellectual, and spiritual aspects. The research method used is qualitative research with a literature review approach. Data were collected by examining authentic hadiths relevant to ethics and methods of seeking knowledge. The analysis was conducted descriptively to identify key themes that can be applied in the development of the Islamic education curriculum. The findings indicate that these principles ethical and methods such as sincere intention, respect for teachers, patience in learning, good time management, and the application of knowledge can be systematically integrated into the curriculum. The integration of these principles not only enhances students' intellectual understanding but also shapes their noble character and deep spiritual awareness. Therefore, Islamic education can fulfill its holistic objective, which is to create individuals who are moral, intelligent, and spiritual.